Land Registration in Indonesia: Between Policy and Legal Certainty - Rahmat Ramadhani; Taufik Hidayat Lubis; Ummi Salamah Lubis; Ismail Koto; Rajarif Syah Akbar Simatupang (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Legal certainty of land is an absolute must to maintain the stability of land use in development and to realize legal certainty of land ownership for people who want to deal with the land. Legal certainty as intended in land registration will result in the granting of a land title certificate by the National Land Agency as an institution that organizes state administration to those entitled, and can be relied on by the owner of his property to act as a strong means of proof of a person's land rights. The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotations, searches for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method which is carried out by presenting the material of legal events or legal products in detail to facilitate interpretation in the discussion. Article 1 paragraph (1) of PP No. 24 of 1997 states that Land Registration is a series of activities carried out by the government continuously, sustainably and regularly, including the collection, processing, opening and presentation as well as maintenance of physical data and legal data in the form of maps and lists regarding land plots and apartment units, including the provision of proof of rights for land plots that already have rights and ownership rights for apartment units with certain rights that burden them. There is an appeal from the government in the context of implementing land registration, namely that the community should not expect the land registration committee to come to survey community lands that have not been registered and then the lands are registered in order to guarantee legal certainty, but the community may on its own initiative gather people or residents whose land does not yet have a certificate and prepare letters or legal basis for ownership of the lands